Managing performance managing people : understanding and improving team performance - Ainsworth, Murray (Pearson Education Australia Franchs ForestAU, 2002)
Explains the reasons behind the high and low performance levels of staff. Focuses on factors that affect these performance levels such as role clarity; competence; values; environment; preference fit; rewards and feedback.